Minimum wage fixing machinery in agriculture. - International Labour Office (Geneva : International Labour Office, 1949)
This book is a report containing the session of a conference by the body of International Labour Office, they decided to placed on the agenda the question "Minimum Wage Fixing Machinery in Agriculture".
At head of title: Report 7 (1)-(2) International Labour Conference. 33d sess., Geneva, 1950.
Corrigendum slip tipped in pt.2.
Includes bibliographical footnotes
hza 25/02/2019
Loans
Keywords: Minimum wage; Agricultural laborers